MUTU GIZI DAN ORGANOLEPTIK SUSU TEMPE FERMENTASI DENGAN PENAMBAHAN JENIS BAHAN PENGENTAL - Luqman Najih; nurhidajah nurhidajah (Jurnal Pangan dan Gizi, 2011)
The aim of the study was to determine the nutritional quality and organoleptic properties of fermented tempe milk with addition of thickening agents. The design study of the mono factors and completely randomized design with 7 treatments and 3 replications, the addition of thickening agents such as flour, tapioca flour, cornstarch, carrageenan, gelatin, agar, and control without the addition of thickening agents. Result: The addition of thickening agents had not significant on pH, ash, protein, and fat, but the significant on the water of fermented tempe milk. Results of statistical analysis of organoleptic test showed addition of thickening agents do not significant the color and aroma but significant on the taste and texture. In terms of nutritional quality, the highest protein total in the tempe milk fermented with the addition of 0.6% gelatin thickening agent (3.635%). The highest fat in the addition of thickening starch 6% (2.214%).